2019
DOI: 10.1007/s42995-019-00001-6
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of iron-reducing bacterial community and iron-reduction activity between riverine and marine sediments in the Yellow River estuary

Abstract: Rivers are the primary contributors of iron and other elements to the global oceans. Iron-reducing bacteria play an important biogeochemical role in coupling the iron and carbon redox cycles. However, the extent of changes in community structures and iron-reduction activities of iron-reducing bacteria in riverine and coastal marine sediments remains unclear. This study presents information on the spatial patterns and relative abundance of iron-reducing bacteria in sediments of the Yellow River estuary and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…However, Firmicutes were also found at elevated levels at several anthropogenically impacted sites (Torres et al, 2019;Haldar and Nazareth, 2018;Tiralerdpanich et al, 2018). While it could be that their presence is due to the pristine nature of the area, it may also be due to the local climate (Nogueira et al, 2015), an unmeasured environmental factor (Tong et al, 2019), or the presence of another organism such as a non-prokaryote or prokaryote which is difficult to detect using 16S rRNA gene amplicon sequencing (Eloe-Fadrosh et al, 2016;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Firmicutes were also found at elevated levels at several anthropogenically impacted sites (Torres et al, 2019;Haldar and Nazareth, 2018;Tiralerdpanich et al, 2018). While it could be that their presence is due to the pristine nature of the area, it may also be due to the local climate (Nogueira et al, 2015), an unmeasured environmental factor (Tong et al, 2019), or the presence of another organism such as a non-prokaryote or prokaryote which is difficult to detect using 16S rRNA gene amplicon sequencing (Eloe-Fadrosh et al, 2016;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that both salinity and organic matter were significantly correlated with communities in different tidal zones, confirming the hypothesis that changes in physicochemical parameters lead to changes in the prokaryotic communities inhabiting these sediments. It has been previously observed that tidal variations can cause nutrient washout or erosion (Behera et al, 2019;Zhang et al, 2020), which in turn can change the bioavailability patterns for organic matter and essential nutrients along the distinct tidal zones of a mangrove habitat. Salinity levels are also influenced by the tidal variations, and it has been previously determined that the increased salinity as well as the prevalence of humic-like substances can interfere with the accessibility of the microbial community to the sediment organic matter (Wang et al, 2010;Ceccon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There could be several explanations for this. In the river, environmental factors and water flow direction differed daily at low and high tide ( Table 2), resulting in diverse environmental stresses on the microbial communities (Böer et al, 2009;Zhang et al, 2020). Changing tides can affect biotic factors such as source communities and species interaction.…”
Section: Factors and Potential Mechanisms Influencing Microeukaryoticmentioning
confidence: 99%